2001
DOI: 10.1046/j.1523-1755.2001.059002754.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cause and time of dropout on the residual GFR: A comparative analysis of the decline of GFR on dialysis

Abstract: The results of our analysis suggest that such informative censoring is independent of treatment modality and that even after correcting for dropout caused by death or transfer to another modality, patients starting on PD have a lower rate of decline in GFR (that is, better preservation of GFR) than patients starting on HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 17 publications
6
97
0
5
Order By: Relevance
“…[15][16][17][18][19] Common features of these trials were that they were underpowered, did not consider nonlinear decline of renal function in their analytic models, and generally enrolled prevalent patients with lower baseline levels of renal function. As with other studies, 22,24 we observed that renal function decline over time was nonlinear, was most marked in the first year of PD, and tended to be slower with biocompatible fluid use in this first year (although not statistically significant). A possible renoprotective benefit of biocompatible (Balance) solution was reinforced by the finding of a significantly delayed onset of anuria (an alternative outcome measure of residual renal function decline) in this group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[15][16][17][18][19] Common features of these trials were that they were underpowered, did not consider nonlinear decline of renal function in their analytic models, and generally enrolled prevalent patients with lower baseline levels of renal function. As with other studies, 22,24 we observed that renal function decline over time was nonlinear, was most marked in the first year of PD, and tended to be slower with biocompatible fluid use in this first year (although not statistically significant). A possible renoprotective benefit of biocompatible (Balance) solution was reinforced by the finding of a significantly delayed onset of anuria (an alternative outcome measure of residual renal function decline) in this group.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the use of a crossover study design to evaluate renal function was problematic, given the nonlinear decline of residual renal function over time. 22,23 Similar difficulties applied to a randomized crossover trial of bicarbonate-buffered dialysate versus conventional dialysate in 55 prevalent PD patients over 12 weeks. 14 More recently, the BalNet study group 12 reported that Balance solution was associated with a nonsignificant slower decline in renal function in 48 incident PD patients in four Korean centers compared with 43 patients receiving stay.safe solution.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no significant difference in 5-year survival of patients in contemporary cohorts, many of the earlier studies have shown a lower risk for death in the first 1-3 years after the start of dialysis. This finding has been attributed to better preservation of native renal function (29). It is possible, although not known, that PD patients may have greater native renal function at the time of transplantation, accounting for the lower risk for death after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning with HD instead of PD has been shown to be related to a faster decline of residual renal function during the fi rst year. [35][36][37][38][39][40] In one study, HD patients experienced more hypotensive episodes due to the intermittent character of this modality in comparison with PD. It can be hypothesized that these episodes have resulted in an accelerated decline of residual renal function in HD patients.…”
Section: Peritoneal Dialysis Versus In-center Hemodialysismentioning
confidence: 99%